Analysis on the Performance of Passenger Terminal Services at I Gusti Ngurah Rai Airport, Bali - I Gede Fery Surya Tapa; I Nyoman Indra Kumara; Dewa Ayu Trisna Adhiswari Wedagama; Decky Cipta Indrashwara (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
I Gusti Ngurah Rai International Airport is one of the busiest airports in Indonesia, due to the increasing number of air transportation service users. This research was conducted to determine the possibility of an increase in passengers every year for 20 years and provide alternative solutions that might be used at this airport if there are facilities that are no longer able to operate maximally. The method used in this research is an analysis of the average and linear trend using time series data from 2013 - 2022, then the method with the smallest standard deviation and the best correlation is chosen, namely the linear trend method. In conclusion, the increase in passengers based on the equation results reaches 3.249% and it causes some facilities to be no longer able to accommodate and operate optimally such as baggage claim devices, gate passport control, and arrival halls. Alternative applicable solutions must be found in these facilities, so that they can work optimally, such as expanding the number of tools and processing early on for gate passport control and generally providing solutions such as reconfiguring the terminal area, peak hour deployment, and technological innovation.